Theories and Concepts of Gifted Children - Nurmanzili; Salami Mahmud (CV Pola Intan Jaya, 2024)
Many gifted children do not receive the educational services that are appropriate for them. By neglecting to provide them with the proper education that they should receive, will make gifted children unable to grow and develop aspects of their talent. Alferd binet proposed the concept of